“Ballet” is a dirty word: Where is ballet in São Paulo? - Rochelle, Henrique [UNESP] (Oxford University Press (OUP), 2021)
Professional dancing in São Paulo, Brazil, developed from the 1950s on, with a constant and strong influence from modern dance. As modernism looked disapprovingly at ballet, seeing it as something from the past, prejudice grew in the city toward the form. Directors and choreographers of dance companies currently speak about ballet and contemporary ballet as something that is done, but always by others, never themselves. Even the word “ballet” is avoided, since it seems to diminish the works being discussed, as it became something strictly associated with dance training, and not professional dance. This chapter investigates the roots of ballet in São Paulo, discussing both its origins and the origins of its rejection, while pointing to the recent indications of its newfound public interest.
Keywords: Ballet; Brazil; Dance training; Modern dance; Modernism; São paulo